THE EFFECT OF CROSSWORD PUZZLE GAME TO THE STUDENTS’ READING SKILL AT GRADE EIGHT OF SMP SWASTA TELADAN PEMATANG SIANTAR - Rotua Manurung, Elsa Lasma; Napitupulu, Selviana; Hutauruk, Bertaria Sohnata (Transpublika Publisher, 2023)
This research explores the impact of utilizing crossword puzzle games as a teaching tool to enhance reading skills, specifically focusing on vocabulary development, among eighth-grade students at SMP Swasta Teladan Pematang Siantar. The study adopts a quasi-experimental quantitative design with a total population of 40 students in the eighth grade. Both the experimental and control groups were subjected to different teaching methods, with the experimental group exposed to crossword puzzle game instruction while the control group received traditional instruction. Vocabulary tests, encompassing synonym and antonym identification through multiple-choice questions, were administered as pre-tests and post-tests for both groups. The findings revealed a substantial increase in the mean score of the experimental group, from 43 in the pre-test to 76.60 in the post-test, compared to the control group's mean score of 42.75 in the pre-test and 67.5 in the post-test. Statistical analysis, employing T-test and t-table values, indicated a significant effect of the crossword puzzle game on reading skills, particularly in vocabulary, among eighth-grade students at SMP Swasta Teladan Pematang Siantar.